High-resolution agriculture image analysis - Lanning, Mark (Kansas State University, 2013)
As the United States government moves forward to regulate commercial use of UAVs for the agricultural industry, the subsequent increased interest in UAVs by farmers and agronomists alike has created a burgeoning need for post-flight image analysis.
Keywords: AgPixel; Unmanned air vehicles; Remote sensing; Image processing; Agriculture